How Effective is European Merger Control? - Thomas Duso; Klaus Gugler; Burcin B. Yurtoglu (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
This paper applies an intuitive approach based on stock market data to a unique dataset of large concentrations during the period 1990-2002 to assess the effectiveness of European merger control. The basic idea is to relate announcement and decision abnormal returns. Under a set of four maintained assumptions, merger control might be interpreted to be effective if rents accruing due to the increased market power observed around the merger announcement are reversed by the antitrust decision, i.e. if there is a negative relation between announcement and decision abnormal returns. To clearly identify the events' competitive effects, we explicitly control for the market expectation about the outcome of the merger control procedure and run several robustness checks to assess the role of our maintained assumptions. We find that only outright prohibitions completely reverse the rents measured around a merger's announcement. On average, remedies seem to be only partially capable of reverting announcement abnormal returns. Yet they seem to be more effective when applied during the first rather than the second investigation phase and in subsamples where our assumptions are more likely to hold. Moreover, the European Commission appears to learn over time.
urn:nbn:de:bvb:19-epub-13200-0
Keywords: L4; K21; G34; C2; L2; 330; Merger Control; Remedies; European Commission; Event Studies; Fusionskontrolle; Wirkungsanalyse; Fusion; Ankündigungseffekt; Börsenkurs; Kapitaleinkommen; Event Study; EU-Staaten